Make A Decision. - Corrigan, Mark (John Wiley & Sons, 2011)
You're the general surgeon on call. It is you who has to decide every course of action over your shift. Make the right decisions or face the consequences ... Taking a role-playing approach, Make A Decision: Surgery allows you to be the book's main character - Dr A. Simpson - a junior general surgeon on call in a busy teaching hospital. Your decisions and actions determine the clinical outcomes of real patients within a number of scenarios. Each scenario branches out and unfolds as you make more decisions, but choose incorrectly and you may be sent home by your boss! Every decision you make is sc.